Factors Affecting Organizational Performance: Mediating Role Of Organization Culture - Nelson, Alden; Fatkhurrahman, Nandana Rizqi Andhika; Rohani, Siti (UNIVED Press, 2026)
This study aims to analyse the factors that influence organizational performance in public service institutions, emphasizing the role of organizational culture as a mediating variable. The independent variables in this study include transformational leadership, organizational innovation, and knowledge management. This study uses a quantitative approach with a non-probability sampling method. Data were collected through the distribution of questionnaires to 276 respondents and analysed using Smart PLS 3 software. The results of the study indicate that all direct relationships between variables are positive and significant. Additionally, organizational culture was found to significantly mediate the influence of transformational leadership, organizational innovation, and knowledge management on organizational performance. These findings underscore the importance of strengthening organizational culture in enhancing the effectiveness and performance of public service institutions in the region. This study provides practical contributions for policymakers and organizational leaders in developing leadership and knowledge management strategies rooted in organizational culture.